PATHOGENESIS, DIAGNOSTICS AND IMMUNOTHERAPY OF IMMUNOPATHOLOGICAL STATES. AUTOIMMUNE DISEASES - Editorial article (SPb RAACI, 2014)
Патогенез, диагностика и иммунотерапия иммунопатологических состояний. Аутоиммунные заболевания.